2022
DOI: 10.1108/ijefm-05-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

The sustainable transformation of business events: sociodemographic variables as determinants of attitudes towards sustainable academic conferences

Abstract: PurposeThis study aimed to assess whether sociodemographic variables explain significant differences in attitudes towards transforming academic conferences into more sustainable events.Design/methodology/approachAn analytical model of participants' attitudes towards sustainable conferences based on literature review as well as the theories of reasoned action and planned behaviour was developed and applied to a sample of 532 surveyed individuals from 68 countries who regularly attended academic conferences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
0
7
0
1
Order By: Relevance
“…Several studies have used the TPB model to explain tourists' intention, many of which were most recently published [7,39,[45][46][47][48][49][50][51][52][53]. For example, Lee and Jan [48] used TPB factors to determine tourists' ecotourism behavioral intention and found that all factors significantly explained intention.…”
Section: Theory Of Planned Behavior and Work Surrounding Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used the TPB model to explain tourists' intention, many of which were most recently published [7,39,[45][46][47][48][49][50][51][52][53]. For example, Lee and Jan [48] used TPB factors to determine tourists' ecotourism behavioral intention and found that all factors significantly explained intention.…”
Section: Theory Of Planned Behavior and Work Surrounding Tourismmentioning
confidence: 99%
“…For example, Lee and Jan [48] used TPB factors to determine tourists' ecotourism behavioral intention and found that all factors significantly explained intention. Santos et al [53] used TPB to assess attitudes as a predictor of environmental behavior in sustainable events. Furthermore, Hsieh et al [29], Hsu and Huang [52], Park et al [50], Cao et al (2020) [45], Sánchez-Cañizares et al [5], Chen and Tung [46], and Seow et al [51] used the TPB and found that all three TPB constructs had a substantial impact on visitors' behavioral intentions.…”
Section: Theory Of Planned Behavior and Work Surrounding Tourismmentioning
confidence: 99%
“…Furthermore, tourism can link different dimensions of sustainability, as it depends on the presence of environments, cultures, and communities (Girard and Nocca, 2017;Martins et al, 2022) and is an important contributor to employment and gross domestic product (GDP) in many countries and regions (Daskin et al, 2020;Rodr ıguez et al, 2020). Moreover, the increasing consumer concern about issues related to biodiversity and sustainability is a clear trend in tourism product policies (Pekers ¸en and Can€ oz, 2022; Santos et al, 2023;Vargas-S anchez, 2018). This highlights the importance of balancing the various aspects of sustainability as one of the main determinants of competitiveness and a critical factor in ensuring long-term sustainable tourism (Einarsson and Sorin, 2020;Girard and Nocca, 2017;Ponte el al., 2021;Santos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…, 2020). Moreover, the increasing consumer concern about issues related to biodiversity and sustainability is a clear trend in tourism product policies (Pekerşen and Canöz, 2022; Santos et al. , 2023; Vargas-Sánchez, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Когда дело доходит до социальной основы устойчивого развития, люди занимают центральное место. Потребности человека должны быть в балансе с потребностями группы (Santos, Fernández-Gámez, Guevara-Plaza, Custódio Santos and Pestana, 2022). И все индивидуумы, группы или общества должны иметь шанс на социальное благополучие в долгосрочной перспективе.…”
unclassified